On the role of the Agulhas system in ocean circulation and climate - Beal, L.; De Ruijter, W.; Biastoch, A.; Zahn, R.; Cronin, M.; Hermes, J.; Lutjeharms, J.; Quartly, G.; Tozuka, T.; Baker-Yeboah, S.; Bornman, T.; Cipollini, P.; et al. (Nature Publishing Group, 2011)
The Atlantic Ocean receives warm, saline water from the Indo-Pacific Ocean through Agulhas leakage around the southern tip of Africa. Recent findings suggest that Agulhas leakage is a crucial component of the climate system and that ongoing increases in leakage under anthropogenic warming could strengthen the Atlantic overturning circulation at a time when warming and accelerated meltwater input in the North Atlantic is predicted to weaken it. Yet in comparison with processes in the North Atlantic, the overall Agulhas system is largely overlooked as a potential climate trigger or feedback mechanism. Detailed modelling experiments-backed by palaeoceanographic and sustained modern observations-are required to establish firmly the role of the Agulhas system in a warming climate. © 2011 Macmillan Publishers Limited. All rights reserved.